2018
DOI: 10.31234/osf.io/5j8zt
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The validity of the online thought-probing procedure of mind wandering is not threatened by variations of probe rate and probe framing

Abstract: Recently, there has been a surge of interest in the measurement of mind-wandering during ongoing tasks. The frequently used online thought-probing procedure (OTPP), in which individuals are probed on whether their thoughts are on-task or not while performing an ongoing task, has repeatedly been criticized, because variations in the frequency of thought probes and the order in which on-task and off-task thoughts are referred to have been shown to affect mind-wandering rates. Hitherto, it is unclear whether this… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 10 publications
2
17
0
Order By: Relevance
“…The reactivity of TUT reports to probing was assessed by four studies. Three tested whether probe rate affected TUT rates: Robison et al (2019) probed subjects after 7% or 13% of task trials, Schubert et al (2020) probed after 3% or 6% of trials, and Seli, Carriere, et al (2013) presented 5-25 probes in a 15-min task . Results varied.…”
Section: Reactivity To Probingmentioning
confidence: 99%
“…The reactivity of TUT reports to probing was assessed by four studies. Three tested whether probe rate affected TUT rates: Robison et al (2019) probed subjects after 7% or 13% of task trials, Schubert et al (2020) probed after 3% or 6% of trials, and Seli, Carriere, et al (2013) presented 5-25 probes in a 15-min task . Results varied.…”
Section: Reactivity To Probingmentioning
confidence: 99%
“…The study had several methodological strengths that we recommend for future studies. It used experience-sampling probes to assess in vivo TUTs, which demonstrate good construct validity (e.g., Kane et al, 2020;Robison et al, 2019;Schubert et al, 2020). We sampled TUT reports from hundreds of students across multiple meetings of multiple courses, reflecting multiple topics, at two universities serving different populations.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Weinstein et al (2018) found that mind wandering was reported more frequently when probes had a mind wandering-positive frame ('my mind was on something other than the text') versus a task-positive frame ('my mind was on the text'). Whereas other methodological artefacts such as probe spacing (Seli et al, 2013) and proberesponse options (Seli, Beaty, et al, 2018) can influence mind wandering responses, Schubert et al (2019) suggest that these factors do not influence the reliability and generalizability of corresponding studies. Thus, if carefully administered, self-reports remain the most viable way to measure an internal phenomenon such as mind wandering.…”
Section: How Is Mind Wandering Measured?mentioning
confidence: 96%
“…Research has indicated that both (probe-and self-caught) methods produce reliable measures (Schubert et al, 2019;Varao-Sousa & Kingstone, 2019) within the limits of self-reporting. For example, mind wandering measures are internally consistent in that within-subject correlations are high (Faber et al, 2018a), they are reliably linked to predictable patterns in physiology (Smallwood et al, 2004), pupillometry (Franklin et al, 2013), eye gaze (Reichle et al, 2010), and they demonstrate predictive validity via negative associations with task performance (Randall et al, 2014).…”
Section: How Is Mind Wandering Measured?mentioning
confidence: 99%